Political economy of national security - Siddiqua-Agha, Ayesha (2002)
This paper highlights the high cost of military security in Pakistan over the past 20 years. With the single agenda of its policy-makers being to neutralise India's military might, defence spending has always got a higher priority than development expenditure. More importantly, the military has had a major role in the division of national resources. The military's role as the key player in power politics and decision-making has allowed it to take a major chunk of the financial pie. - Reproduced.
Keywords: State security - Pakistan; State security